1992
DOI: 10.21273/jashs.117.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Genotype, Temperature, and Fall-applied Ethephon Affect Plum Flower Bud Development and Ovule Longevity

Abstract: Flower bud growth and ovule longevity of plum (Prunus domestics L.) cultivars Italian and Brooks and the effects of fall-applied ethephon and of temperature were studied. Fresh and dry weights of terminal flower buds were measured at l-week intervals from 50 days to 1 day before bloom in 1988. Buds were also analyzed for N, P, K, Ca, and B. After bloom, ovule longevity was determined using a fluorescence method after staining with aniline blue. Ovule longevity was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…High temperatures at bloom clearly reduced potential yield. This finding agrees with that of Moreno et al (1992), who found that increasing temperatures induced faster ovule senescence and consequently reduced fruit set. These two cultivars are considered to have a high chilling requirement because of their late bloom dates (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…High temperatures at bloom clearly reduced potential yield. This finding agrees with that of Moreno et al (1992), who found that increasing temperatures induced faster ovule senescence and consequently reduced fruit set. These two cultivars are considered to have a high chilling requirement because of their late bloom dates (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In those years when temperatures during bloom were lower and higher than a PC value of 0.4, yields were reduced, suggesting that it is an optimum temperature for fruit set. High temperatures reduce ovule longevity (Moreno et al, 1992) and low temperatures retard pollen tube growth (Williams, 1970); therefore, fruit set can be diminished by a failure in fertilization derived from inappropriate temperatures at bloom. This cultivar group had the lowest chilling requirement, 700 chill units (Richardson et al, 1974), which can be supported by the fact that these trees bloomed earlier than cultivars in the other groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When pollen arrives on the stigma, it induces ethylene production (Johnson and Polito, 2007), which has been reported to induce the arrest of ovule development (Zhang and O'Neill, 1993). Female sterility in Prunus can be also induced by the application of different external chemical treatments (Beppu et al, 2001;Herrero et al, 2000;Morenol et al, 1992;Stösser and Anvari, 1982). Regardless of the factor causing ovule degeneration, it seems that different genotypes have a different response, because in one of the orchards analyzed, other cultivars had normal fruit sets (data not shown).…”
Section: Discussionmentioning
confidence: 99%